Application of TCE-PCM based heat sinks for cooling of electronic components: A review. (June 2016) - Sahoo, Santosh Kumar; Das, Mihir Kumar; Rath, Prasenjit
Abstract: Generally, the commercial and industrial electronic devices are required to be operated under 100 °C.Therefore, there is a need to remove heat effectively from these devices under different loading conditions. Till now, Phase Change Material (PCM) based heat sinks are emerging as one of the effective techniques for removal of heat from the electronic devices. However, the low thermal conductivity of PCM situates a hindrance to the development. Thus, current research focuses on improving the thermal performance of PCM using thermal conductivity enhancer (TCE). At present internal fins, metallic foams and nano particles are mixed with PCM to enhance the performance of heat sinks. These are called as thermal conductivity enhancers. This article reviews methodologically various papers on the methods used for enhancement of PCM performance in cooling of electronic components. The effect of various parameters influencing the performance of the TCE-PCM based heat sinks are discussed in systematic order. The performance of these heat sinks under constant and variable thermal load are also evaluated. Out of these three TCE, metallic foams in heat sinks provides a higher surface area to volume ratio, good thermal conductivity and considerable weight advantage.